Teaching Preschoolers Theory of Mind Skills With Mobile Games - Nikolayev, Mariya; Evmenova, Anya S.; Reich, Stephanie M.; Clark, Kevin A.; Burns, M. Susan (Frontiers in Education, 2022)
This single-case research study examined whether interactive touch screen apps enriched with Theory of Mind (ToM)—enhancing language would promote ToM skills in preschoolers. Six typically developing girls between the ages of 46- and 52- months participated in multiple sessions across the three phases of the study: In baseline, participants played games without voice-overs; in the original treatment phase, participants played games with embedded voice-overs; finally, in the modified treatment phase, participants first played games with embedded voice-overs, then engaged in the researcher-led conversation. All sessions across the three phases concluded with ToM assessments: two measures based on a continuous scale. The first measure included three tasks targeting earlier-developing ToM skills (diverse desires, diverse beliefs, and knowledge access), and the other measure had two tasks that assessed a later-developing ToM competency, false belief understanding. Results showed that apps with ToM-embedded language improved children’s earlier-developing ToM skills (i.e., understanding that people can have different desires, beliefs, and knowledge access) in the phase where an adult-led conversation also followed voice-over-enriched app play. Apps with ToM-embedded language without a follow-up discussion were only marginally effective in promoting the earlier-emerging ToM skills. Across the conditions, apps were not effective in promoting children’s later-developing ToM skills—false belief understanding. Our findings indicate that incorporating ToM conducive language in mobile apps can promote ToM development in preschoolers, especially when supplemented by an adult-led conversation.